Consumption of Moringa oleifera flour and its effects on the biochemical profile and intestinal motility in an animal model - Elen Landgraf Guiguer; Sandra Maria Barbalho; Paulo Sergio Marinelli; Patricia Cincotto Bueno; Patricia Cincotto Bueno; Claudemir Gregorio Mendes; Mirele Cristina Santos; Leticia Maria Salzedas; Marie Oshiiwa; Manoel Lima Mendes; Claudia Teixeira Nicolau; Alda Maria Otoboni (International Journal of Phytomedicine, 2016)
Moringa oleifera (MO) belongs to the family Moringaceae and is native to tropical Africa. It exhibits many therapeutic properties and has been widely cultivated because of the high food value of the leaves, fruit, flowers and roasted seeds. It possesses high quality protein, calcium, iron, fiber, minerals and essential amino acids. The objective of this study was to evaluate the effects of MO flour in anthropometric and biochemical profile of Wistar rats. Animals were divided randomly into the following groups (n=10): G1 (control group) and G2 (treated with MO flour mixed to the rat food) were both treated for 40 days and G3 (control group), G4 (treated with senne) and G5 (treated with MO flour) were studied to evaluate the intestinal motility. After 40 days, animals of G1 and G2 were euthanized and evaluation of glycaemia, total cholesterol, triglycerides, LDL-c, VLDL-c, HDL-c, C reactive Protein (PCR), hepatic enzymes, Lee Index, weight and visceral fat were performed. Our results showed reduction of visceral fat, total cholesterol, triglycerides, LDL-c, and VLDL-c and increase in the HDL-c levels. No significant differences were found in the body weight, glycaemia, hepatic enzymes and PCR. The MO flour also promoted laxative effects similar do senne. Our results with the use of Moringa oleifera flour are very promising, once its use improved lipid profile, prevented weight gain and showed no adverse effects. Thus we may conclude that this flour could be added to industrial products in order to provide healthier products to the consumers.